In-Situ Synthesis of Active Pharmaceutical Ingredients Which Content Pyrazole Skeleton - Pathan, Sultan; Repale, Anil; Pal, Girdhar (Letters in Organic Chemistry, 2020)
Celecoxib containing pyrazole derivatives were synthesized by path aldol condensation of substituted ketone with trifluoroethyl acetate subsequently by cyclization of the formed chalcones with 4-methanesulfonylphenylhydrazine. Here, a one-pot synthesis of celecoxib and substituted analogues have been reported which are nonsteroidal anti-inflammatory drugs for their cyclooxygenase (COX) inhibition, anti-inflammatory activity and ulcerogenic liability. In order to intermediate work-up, a continuous one-pot synthesis has been developed, performing the entire reaction sequence that results in a shorter time with good yield.
Keywords: COX-2